Unaccusative Verbs and Their Syntactic Correlates in New Brunswick Acadian French - Balcom, Patricia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2005)
Labelle (1992) argued that pronominal change-of-state verbs in French are unaccusative while those without se are unergative, since the former are conjugated with être in compound tenses, as are unaccusative verbs of inherently directed motion. On the other hand, change-of-state verbs without se are conjugated with avoir in compound tenses, like unergative activity verbs. Both verbs of inherently directed motion and pronominal change-of-state verbs occur in impersonal constructions, but change-of-state verbs without se are ungrammatical in such constructions, as are other unergative verbs. A third characteristic of verbs of inherently directed motion in French is that, unlike English and Spanish, their past participles can appear in DPs, for example [DP les invités arrivés après moi]. Borgonovo and Cummins (1999) attribute this to the fact that they are conjugated with être. It remains to be seen whether the syntactic correlates of unaccusativity described above exist in Acadian French, where use of avoir has been demonstrated to be categorical with both verbs of inherently directed motion and pronominal change-of-state verbs (Gesner 1978, Péronnet 1991, King and Nadasdi 2001). I will explore this question using a fill-in-the-blanks task (FB) and grammaticality judgement (GJ) task. The FB is a narrative in the past with blanks to be filled in with an appropriate form of the verb in parentheses. It includes unaccusative verbs (change of state and inherently directed motion), as well as transitive and unergative verbs (change of state and activity). The GJ uses the same verbs as the FB and contain sentences exemplifying the syntactic correlates of unaccusativity. Subjects were speakers of Acadian French from northeastern and southeastern New Brunswick. They were first-year students at a Francophone university in the maritime provinces of Canada. Results indicate that they used être 100% of the time with pronominal change-of-state verbs, but variably with verbs of inherently directed motion. Their acceptance of the syntactic correlates of unaccusativity was also variable. There was a relationship between subjects’ acceptance of conjugation with être in compound tenses and their acceptance of impersonal il constructions and past participles in DPs. No significant regional differences were found.